A stable zirconium based metal-organic framework for specific recognition of representative polychlorinated dibenzo-p-dioxin molecules - Wang, Bin; Wang, Peilong; Xie, Lin-Hua; Lin, Rui-Biao; Lv, Jie; Li, Jian-Rong; Chen, Banglin (Nature communications, 2019)
Polychlorinated dibenzo- p -dioxins (PCDDs), as a class of persistent and highly toxic organic pollutants, have been posing a great threat to human health and the environment. The sensing of these compounds is important but challenging. Here, we report a highly stable zirconium-based metal-organic framework (MOF), Zr 6 O 4 (OH) 8 (HCOO) 2 (CPTTA) 2 (BUT-17) with one-dimensional hexagonal channels and phenyl-rich pore surfaces for the recognition and sensing of two representative PCDDs, 2,3-dichlorodibenzo- p -dioxin (BCDD) and 2,3,7,8-tetrachlorodibenzo- p -dioxin (TCDD), based on the fluorescence quenching. BUT-17 exhibits high sensing ability with the detection limits as low as 27 and 57 part per billion toward BCDD and TCDD, respectively, and is very selective as well without the interference of similar compounds. The recognition of BUT-17 toward BCDD is demonstrated by single-crystal structure of its guest-loaded phase, in which the fluorescence-quenched complexes form between the adsorbed BCDD molecules and the MOF host through π-π stacking and hydrogen bonding interactions. The sensing of polychlorinated dibenzo- p -dioxins (PCDDs) is important for the environment and public health but challenging to achieve. Here the authors report a stable zirconium-based metal-organic framework for the selective sensing of two representative PCCDs based on the fluorescence quenching method.